2011
DOI: 10.4103/0974-2727.86839
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of Synovial Lipomatosis and its Clinical Significance

Abstract: Background:Synovial lipomatosis is a rare disorder of the synovium, commonly affecting the knee joint, resulting in joint pain, swelling, and effusion. The etiology of this condition still remains unclear.Aim:This was a study done to evaluate the disease process in synovial lipomatosis, with respect to the clinical parameters and pathological features.Materials and Methods:Case files of synovial lipomatosis diagnosed on histopathology between 2007 and 2009 were perused, to study the case history, and tissue se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(69 citation statements)
references
References 13 publications
(18 reference statements)
1
67
0
Order By: Relevance
“…Rao et al reported that among the eight patients studied in their series, four had high BMI and one had low BMI. 23 The mean BMI was 28.3 AE 3.38 in our study. None of the patients was underweight.…”
Section: Discussionsupporting
confidence: 41%
“…Rao et al reported that among the eight patients studied in their series, four had high BMI and one had low BMI. 23 The mean BMI was 28.3 AE 3.38 in our study. None of the patients was underweight.…”
Section: Discussionsupporting
confidence: 41%
“…The histomorphology of synovial lipomatosis is associated with adipocyte metaplasia and inflammation, and fibrosis (16); thus, synovial lipomatosis can be more accurately described as the process of overgrowth and infiltration of mature adipose tissue within the synovium. Occasionally, fibrous septa may be visible between the vascular channels and adipose tissue within the lesion (17).…”
Section: Discussionmentioning
confidence: 99%
“…11 Al ismail et al 12 and Hubscher et al 13 had also proposed inflammation and mechanical factors in etiopathogenesis of osteoarthritis secondary to lipoma arborescens. Rao et al 14 had proposed that LA could result from inappropriate fat deposition and degenerative disease of the joints. Moreover, the cases described in literature were of older age group in which the osteoarthritis is as such common.…”
Section: Discussionmentioning
confidence: 99%